Cytotoxic Activity of Eugenia polyantha Wight Young Leaves Purification Extract and Fraction on T47D - Hidayati, Devi Nisa; Safitri, Erika Indah; Yumni, Gharsina Ghaisani; Salsabiila, Iqna; Rahayu, Putri (Jurnal Kefarmasian Indonesia, 2023)
Breast cancer is a cancer that ranks the highest incidence in Indonesia. One of the plants that can be used for this treatment is a bay leaf (Eugenia polyantha Wight). Purification techniques can optimize the extraction of flavonoid compounds to create larger concentrations of these substances. Old bay leaves' ethyl acetate fraction has lethal effects on T47D cancer cells. In this work, the amounts of flavonoids and the cytotoxic activity of young bay leaves' pure extract and ethyl acetate fraction against T47D cells are to be determined. By using the maceration process, two phases of methanol extraction from young bay leaves were produced. In the first stage, ethyl acetate was used to partially purify the material, and in the second stage, n-hexane, ethyl acetate, and water. Cytotoxic tests of purified extract and ethyl acetate fraction of young bay leaves were carried out at 200; 350; 500; 750; and 1000 µg/mL. Cytotoxicity test using the MTT assay method. IC50 value analysis using linear regression. Determination of total flavonoid content using a UV-Visible spectrophotometer with a comparator compound, quercetin. The results showed that the purified extract of young bay leaves and the ethyl acetate fraction of methanol extract of young bay leaves had cytotoxic activity with IC50 values of 570.57 ± 30.72 µg/mL and  588.45 ± 6.90 µg/mL, respectively. Total flavonoid levels were 9.80 ± 0.05 mgQE/g and 5.99 ± 0.06 mgQE/g.The purified extract and ethyl acetate fraction on young bay leaf extract (Eugenia polyantha Wight) had cytotoxic activity on T47D cells and the highest levels of flavonoids in the purified extract.